Edukasi untuk Meningkatkan Pengetahuan Mahasiswa Tentang Diabetes Mellitus Tipe-2 - Devi Savitri Effendy; Sri Kaltsum Fadilat. AR; Nilam Husnul Khatima; Ninda Garnawati; Amalia Darma Munandar; Yonathan Mendila; Harleli Harleli; Febriana Muchtar; Hariati Lestari; Hartati Bahar; Suhadi Suhadi (PPNI UNIMMAN, 2024)
Diabetes mellitus (DM) is a metabolic disease whose prevalence is increasing due to changes in lifestyle, especially among the younger generation, including students. Unhealthy habits such as a high-calorie diet, lack of physical activity, and high levels of stress can increase the risk of developing DM. Currently, DM is the seventh leading cause of death worldwide, with type 2 diabetes mellitus (T2DM) being the largest cause of death. Based on the Southeast Sulawesi Health Profile, DM is ranked fifth out of the ten most common diseases in Southeast Sulawesi with a total of 13,946 sufferers. The increase in the number of people with type 2 diabetes mellitus is a serious global health threat. Therefore, it is important to prevent the prevalence of DM through preventive and promotive actions. One promotional activity that can be carried out is to educate, encourage change and increase knowledge about healthy lifestyles so that the occurrence of disease or bad health conditions in the future can be prevented.